Dinámicas campesinas y fitomejoramiento participativo : El caso de los sorgos blancos (Sorghum bicolor, L. Moench) en la región norte de Nicaragua - Trouche, G.; Hocde, H; Aguirre Acuña, S.; Martínez Sanchez, F.; Gutiérrez Palacios, N.D. (2006)
Farmers dynamics and participatory plant breeding: the case of white grain sorghums in the Northern region of Nicaragua. In the dry areas of Nicaragua, white grain sorghums are an important food crop for the poor farmers. Since 2002, CIRAD and CIAT manage in collaboration with NGOs and local experimenter farmers' groups a research project on sorghum participatory breeding addressed to the low-resources farmers. In this paper, the authors describe the start of the project in the Madriz department, North of Nicaragua, and indicate the most relevant results of this preliminary phase. This work started with an intensive participatory diagnostic about the cropping systems, the varieties, the production constraints, the sorghum utilizations and a pre-definition of the breeding objectives. The participants and practices of the seed production and exchanges were identified. At the same time, the local varieties of tortillero and millón sorghum were characterized for morphological and agronomic traits. Among the results emerge the recent changes concerning the varieties and the cropping systems, the rapid adoption of the short-cycle tortillero sorghum by the mean of informal processes of seed exchanges; the original traits of the millón varieties, like their extreme sensitivity to photoperiod, have been quantified. These data were used for implementing the activities of participatory variety selection and for choosing the parents and crosses for the participatory breeding schemes. As perspectives, the authors propose to integrate more this process of participatory breeding within the endogenous projects strengthening the family agriculture with an agro-ecological focus and extend it to other themes, crops and areas in an inter-institutional framework of research-action for small farmers in marginal areas.